Environmental Impacts and Economic Implications of Phosphorus Recovery - Sena, Madeline (My University, 2019)
The impact of excessive nutrient loading from phosphorus (P) and nitrogen (N) is one of the most pervasive and challenging environmental issues in the United States. However, with growing concern for the longevity of global phosphate rock stores there is also interest in recovering these nutrients. One potential piece of sustainable nutrient management is the recovery of P and N from wastewater through the precipitation of magnesium ammonium phosphate (NH4MgPO4 ∙ 6H2O), or struvite. However, a potential concern is that the environmental impacts struvite recovery creates through the use of additional chemicals and energy are not offset by its benefits. A well-established method for assessing the environmental impacts of products and processes is life cycle assessment (LCA), which can provide information about impacts in a variety of different environmental categories. In conventional decision making processes these environmental impacts are usually only a small part of the consideration with economic factors driving the decision making. However, this traditional approach neglects the significant potential environmental impacts these nutrient management decisions can have. One way to incorporate environmental impacts of nutrient pollution specifically into decision making processes is through the monetary valuation of nutrients or the damage they can cause. This research focuses on evaluating the environmental performance of struvite recovery as a nutrient management technology in wastewater treatment through LCA and understanding how the environmental considerations of nutrient management technologies can be incorporated into conventional decision making through monetary valuation. Chapter one outlines the specific objectives that are addressed through this research. In the second chapter, LCA literature on struvite recovery systems in wastewater treatment was reviewed to understand the current state of knowledge and identify gaps and inconsistencies in the body of literature. Analysis highlighted a lack of studies assessing full scale systems in locations outside of Europe despite knowledge of a growing number of operations in the United States specifically. Additionally, the emergence of a new trend in functional units in terms of an amount of nutrients recovered was identified, and it was recommended in future research to evaluate over two functional units to complement both the nutrient recovery and wastewater treatment perspectives of these struvite recovery systems. The third chapter is a LCA of a struvite recovery system at the Nine Springs Wastewater Treatment Plant (WWTP) in Madison, WI USA which attempts to fill the gap identified in the previous literature review. This assessment finds that the implementation of struvite recovery system improved the overall environmental performance of the WWTP as a whole. Additionally, the operation of the struvite system on its own is found to have a net neutral or slightly positive environmental impact, and overall improvement in the amount of chemicals or use of alternative chemicals in the recovery process is highlighted as an area of focus in future research. The fourth chapter surveys literature on the economic damages of nutrient pollution and monetary valuation of P in the environment to understand any gaps and areas for improvement in incorporating economic impacts or damages into decision making processes. Different estimations of the cost of P in the environment were assessed based on a collection of literature studies, and these values were then applied in a case study to demonstrate how the variability in these estimates can affect decision making. Additionally, recommendations were made for future work to focus on how to combine and weight different valuation methods, and for the establishment of a standardized method for assessing the value of nutrients. In conclusion, this body of work assesses the environmental impacts of struvite recovery in wastewater treatment as a nutrient management option, and explores the use of monetary valuation as a way to incorporate the environmental impacts of nutrient management solutions into conventional decision making processes. While there still remains opportunities for further research into the environmental impacts of other nutrient recovery systems and advancement in the incorporation of environmental considerations into decision making processes this work fills several gaps in the body of knowledge surrounding nutrient management solutions.
Keywords: life cycle assessment; wastewater; nutrient recovery; struvite